Functionally Modified Polyolefin-Based Separators for Lithium-Sulfur Batteries: Progress and Prospects - Li, Jiaojiao; Xiao, Zhen; Chen, Anqi; Zhang, Wenkui; Zhu, Dongmin; Jin, Yanxian; Mao, Qinzhong; Wang, Guoguang; He, Jiarui; Xia, Yang (Frontiers in Energy Research, 2020)
The ever-growing demand for portable devices and electric vehicles are drawing widespread attention to advanced energy storage systems. Over the past few decades, lithium-sulfur batteries (LSBs) have vast potential to act as the next-generation of rechargeable power source due to their high theoretical specific energy, cost-effectiveness, and environmental benignity. However, insufficient sulfur utilization, inferior cyclability, and rate capability originating from the intrinsic insulating features of the sulfur and notorious polysulfide shuttle are major obstacles to fulfilling the industrialization of LSBs. In this respect, the introduction of a functional barrier layer coating on a separator has been verified as an effective strategy to overcome the aforementioned intractable problems. In this review, we focus on summarizing the current progress of the modified polyolefin-based separators (known as functional separators), including functional separator facing cathodes and functional separator facing anodes. According to the working mechanism, functional separator facing cathodes are divided into physical adsorption separators, chemical adsorption separators, catalytic conversion separators, and multifunctional separators. Meanwhile, functional separator facing anodes are classified into physical barrier separators, induced lithium growth separators, regulated lithium nucleation separators, and hybrid mechanism separators. Finally, the future perspective coupled with the practical utilization of functional separators in LSBs is proposed.